2004
DOI: 10.1111/j.1600-079x.2004.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Pinealectomy exaggerates and melatonin treatment suppresses neuroma formation of transected sciatic nerve in rats: gross morphological, histological and stereological analysis

Abstract: At present, an intensive effort for prevention of neuroma formation following peripheral nerve section continues. It has been recently suggested that surgical pinealectomy (Px) induces elevation of the collagen content in the granulation tissue of a wound, while melatonin application after Px suppresses elevation of the collagen accumulation in the tissue. The aim of the present study was to assess whether melatonin had the ability to suppress collagen production and neuroma formation following peripheral nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
(69 reference statements)
2
36
0
1
Order By: Relevance
“…Organizmanın bu süreçle savaşta, antioksidan sistemleri devreye soktuğu bilinmektedir 9 . Yapılan araştırmalar melatoninin, antioksidan defans sistemlerinden biri olduğunu göstermektedir [10][11][12] . Diğer yandan, organizmadaki birçok fonksiyon düzenli olarak tekrarlayan bir organizasyon içinde olup, bu değişikler "biyolojik ritimler" olarak adlandırılmaktadır.…”
Section: Introductionunclassified
“…Organizmanın bu süreçle savaşta, antioksidan sistemleri devreye soktuğu bilinmektedir 9 . Yapılan araştırmalar melatoninin, antioksidan defans sistemlerinden biri olduğunu göstermektedir [10][11][12] . Diğer yandan, organizmadaki birçok fonksiyon düzenli olarak tekrarlayan bir organizasyon içinde olup, bu değişikler "biyolojik ritimler" olarak adlandırılmaktadır.…”
Section: Introductionunclassified
“…It has the ability to protect DNA against oxidative damage and may also have strong antiinflammatory effects (Genovese et al, 2005). In recent years, MLT has been indicated as having a neuroprotective effect upon a variety of neuropathological events such as ischemia, infarction, and edema formation (Pei et al, 2002;Reiter et al, 2001;Turgut et al, 2005a;Turgut et al, 2005b). Based on these data, it was expected that MLT, given during the prenatal period, may ameliorate the developmental damage to the PNS, and the disruption of nerve myelination, caused by ETH toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The functional recovery of damaged nerves was estimated by the amount of Schwann cells and the number of re-innervated muscle motor end-plate targets [117]. Furthermore, it is worth mentioning that Turgut et al have experimentally demonstrated in rats that melatonin prevents neuroma formation after transacting the sciatic nerve by enhancing axonal regeneration [118]. Recently, some studies have shown the positive effect of melatonin on preventing scar formation, increasing nerve regeneration and improving functional recovery [119,120].…”
Section: Melatoninmentioning
confidence: 99%
“…Turgut et al examined the gross morphology of neuroma formation in the proximal nerve segment via macroscopic and microscopic findings, and the surgical pinealectomy group without application of melatonin caused a proliferation of connective tissue and large neuroma formation at the proximal ends of transacted nerves compared with the surgical pinealectomy group and the group given melatonin (P < 0.005) [118]. In addition, Kaya et al demonstrated a beneficial effect on axonal regeneration and functional recovery in the experimental group in which melatonin was applied after stripping of the epineurial vessels compared with other groups without melatonin application [119].…”
Section: Mechanisms Of Action Referencesmentioning
confidence: 99%
See 1 more Smart Citation